Management of Communication Media of Regional Disaster Management Agency in Mitigating the Impact of Covid19 Omicron Variant in South Kalimantan - Putri Ayu Hidayatur Rafiqoh; Widyakanti Widyakanti (Hut Publication Business and Management, 2022)
The spread of the new variant of the COVID-19 virus is a continuous polemic in the community. The South Kalimantan government has taken more action to handle it by managing the communication media so that people don't panic about this new variant. This study discusses the Regional Disaster Management Agency (BPBD) Disaster Communication Model in Combating the Spread of the Omicron Variant of Covid-19 in South Kalimantan. This study refers to the theory of Disaster Communication in which there are several indicators with the following results; Planning, the South Kalimantan BPBD in collaboration with the South Kalimantan Communication and Information Technology and the Covid-19 task force in managing information related to Covid-19. Then, Organizing is dividing the tasks in each field to respond to the pandemic situation. Furthermore, Actuating is a communication media that is managed in an integrated manner by the Communication and Information Technology of South Kalimantan province. And the last one is Controlling, which is listening to the possibility of a response from the community so that all forms of response and answers that are given depend on the intended field.